Assessing residue and tillage management options for carbon sequestration in future climate change scenarios - Aditi, Kumari; Abbhishek, Kumar; Chander, Girish; Singh, Ajay; Falk, Thomas; Mequanint, Melesse B.; Cuba, Perumal; Anupama, G.; Mandpati, Roja; Nagaraji, Satish (Elsevier, 2023)
Soil carbon depletion is a major concern for food security in drylands. The objective of this study is to test tillage with residue management under sequential and intercropping systems for carbon sequestration in semi-arid tropical drylands of India. We report the findings from a long-term field experiment (9 years) used to simulate the effect of residue and tillage management in Maize-chickpea sequential and Maize-Pigeonpea intercropping systems for the four possible future climate projections using APSIM model. These findings demonstrate a sustainable route with inclusive growth, as pledged at the UN climate change summit. A comparison of results under SSP 2.6 and 4.5 Wm−2 with SSP 8.5 shows that demand pressure from competitive marketplaces inhibits the establishment of soil carbon sinks and significantly reduces crop yields, likely due to indiscriminate chemical fertilizer use. We observed that a better decision in selecting cropping system might improve soil organic carbon content (SOC). SOC content ranging from 0.9 to 1.2% in Maize-pigeonpea intercropping and 0.85–1.1% in maize-chickpea sequential cropping systems, demonstrate good potential in the climate change mitigation exertions. Early SOC saturation (20 years) led to a decreased carbon stock in topsoil without residue addition practises. The addition of crop residues significantly increased SOC levels under both conventional and minimum tillage and created additional income for farmers. Simulation analysis showed impact of SOC changes on crop yield which remained nearly stable for 85 years. Therefore, hardy straw biomass of crops covering a large tract in dryland tropics, can be a scalable and sustainable solution to yield losses, while mitigating climate change through carbon sequestration.